A validated LC-ESI-MS/MS assay for simultaneous plasma quantification of 11 antimicrobials to support personalized dosing in critically ill children - Zhang, Yuan-Yuan; Wang, Jie; Guo, Hong-Li; Wu, Shi-Yu; Zhang, Hai-Feng; Zheng, Peng-Fei; Miao, Hong-Jun; Chen, Feng (Frontiers in Molecular Biosciences, 2026)
IntroductionCritically ill patients with severe infections demonstrate profound alterations in pharmacokinetic behavior. Therapeutic drug monitoring (TDM)-informed antimicrobial dose optimization is thus essential in intensive care settings to ensure maximal bactericidal activity while mitigating toxicity, creating an urgent need for accessible analytical methodologies. Although various studies exist in this domain, the inherent technical constraints of current methodologies persistently prevent the full resolution of these unmet clinical requirements.MethodsA rapid and sensitive LC-ESI-MS/MS method was developed and validated for the simultaneous quantification of 11 antimicrobials in human plasma. Sample preparation was performed by a simple one-step protein precipitation using methanol containing 0.1% formic acid. The analytes were separated on a Kinetex C18 column with a “corner-folded cleaver-shaped” gradient elution program and detected using multiple reaction monitoring (MRM) in positive ionization mode.Results and DiscussionThe gradient elution program achieved baseline separation of all tested analytes within 8 min, with symmetrical peak shapes and no endogenous interference. The developed method was proven to be free of matrix effects, excellent linearity (R2 > 0.99 for all analytes), and met international bioanalytical validation criteria across clinically relevant concentration ranges. Notably, this validated method was successfully applied to children receiving mono- or combination therapy for infections. The assay meets requirements for clinical TDM implementation, providing pediatricians with reliable antibiotic concentration measurements within a clinically relevant timeframe.